Convergent evolution of perenniality in rice and sorghum - Hu, F.Y.; Tao, D.Y.; Sacks, E.; Fu, B.Y.; Xu, P.; Li, J.; Yang, Yang; McNally, K.; Khush, G.S.; Paterson, A.H.; Li, Z.K. (National Academy of Sciences, 2003)
Annual and perennial habit are two major strategies by which grasses adapt to seasonal environmental change, and these distinguish cultivated cereals from their wild relatives. Rhizomatousness, a key trait contributing to perenniality, was investigated by using an F 2 population from a cross between cultivated rice ( Oryza sativa ) and its wild relative, Oryza longistaminata . Molecular mapping based on a complete simple sequence-repeat map revealed two dominant-complementary genes controlling rhizomatousness. Rhz3 was mapped to the interval between markers OSR16 [1.3 centimorgans (cM)] and OSR13 (8.1 cM) on rice chromosome 4 and Rhz2 located between RM119 (2.2 cM) and RM273 (7.4 cM) on chromosome 3. Comparative mapping indicated that each gene closely corresponds to major quantitative trait loci (QTLs) controlling rhizomatousness in Sorghum propinquum , a wild relative of cultivated sorghum. Correspondence of these genes in rice and sorghum, which diverged from a common ancestor ≈50 million years ago, suggests that the two genes may be key regulators of rhizome development in many Poaceae. Many additional QTLs affecting abundance of rhizomes in O. longistaminata were identified, most of which also corresponded to the locations of S. propinquum QTLs. Convergent evolution of independent mutations at, in some cases, corresponding genes may have been responsible for the evolution of annual cereals from perennial wild grasses. DNA markers closely linked to Rhz2 and Rhz3 will facilitate cloning of the genes, which may contribute significantly to our understanding of grass evolution, advance opportunities to develop perennial cereals, and offer insights into environmentally benign weed-control strategies.